Straffuldbyrdelsesloven - Vagn Greve (Nordisk Tidsskrift for Kriminalvidenskab)
Until now, the prison administration in Denmark has regulated the actual content of prison, parole, and conditional sentences. In accordance with the rule of law, Parliament has now passed an act on the execution of sentences containing principles for execution and a bill of rights for convicts. This article provides an overview of the basic ideas in this act. At the same time, Parliament abolished the special sanction of lenient imprisonment, made new rules for traffic fines, and introduced specific time limits on the use of treatment sanctions for mentally deviant persons in closed institutions.